2015
DOI: 10.1093/jac/dkv220
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for antimicrobial resistance in Australian isolates ofClostridium difficile, 2013–14

Abstract: These data confirm the potent in vitro activity of fidaxomicin against C. difficile. Moreover, this study provides an important baseline for ongoing long-term surveillance of antimicrobial resistance and prospective tracking of prominent and emerging strain types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
49
4
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 38 publications
12
49
4
2
Order By: Relevance
“…C. difficile culture was performed as previously described (Knight et al, 2015b). After subculture on blood agar for 24 h, 1–3 colonies of each isolate were inoculated into pre-reduced brain-heart infusion broth containing 0.1% L-Cysteine and incubated anaerobically at 37°C overnight (~16 h).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…C. difficile culture was performed as previously described (Knight et al, 2015b). After subculture on blood agar for 24 h, 1–3 colonies of each isolate were inoculated into pre-reduced brain-heart infusion broth containing 0.1% L-Cysteine and incubated anaerobically at 37°C overnight (~16 h).…”
Section: Methodsmentioning
confidence: 99%
“…Minimum inhibitory concentrations (MIC) were determined for a panel of 16 antimicrobial agents against all RT014 isolates ( n = 40) using CLSI agar dilution methodology as previously described (Knight et al, 2015b). The panel included vancomycin, metronidazole, fidaxomicin, rifaximin, clindamycin, erythromycin, amoxicillin-clavulanate, piperacillin-tazobactam, ceftriaxone, meropenem, moxifloxacin, tetracycline, trimethoprim, gentamicin, tobramycin, and spectinomycin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…C. difficile RT033 was previously detected in the patient's stool sample; thus, it was possible that this ribotype was responsible for the CDT-positive result obtained. Susceptibility testing using an agar dilution method and CLSI/EUCAST in-terpretive criteria (2) showed that both RTs were susceptible to clindamycin, moxifloxacin, metronidazole, and vancomycin. The MICs of fidaxomicin and rifaximin were 0.06 mg/liter and 0.004 mg/liter, respectively.…”
mentioning
confidence: 99%